The use of ultrasound in endodontics: A literature review (Research, Society and Development, 2023)
The use of ultrasonic equipment as an auxiliary resource in Endodontic Treatment, in recent years, has increased and demonstrated to be effective. Based on this, the objective of this work is to identify the main literature findings on the use of ultrasound as an aid in endodontic therapy. This work is a bibliographical review of the literature with a qualitative approach, with articles selected from the PubMed, Bireme databases and teaching materials, published in Portuguese and English. It was found that, due to the emission of high frequency waves, the technique provides agility in the treatment, making it more comfortable for the professionals involved. The ability to work in difficult-to-access areas, such as narrow root canals, allows for more effective cleaning, removing debris and microbial residues, which contributes to the success of endodontic treatment. The use of ultrasound, as an aid in endodontic therapy, offers substantial benefits, becoming a valuable tool for Dentistry, considering the increase in effectiveness and reduction of treatment time, as well as providing greater comfort during endodontic procedures, which reinforces its growing importance in clinical practice.